Developing a long-term high-resolution winter fog climatology over south Asia using satellite observations from 2002 to 2020 - Singh, Manoj K.; Gautam, Ritesh (Remote sensing of environment, 2022)
The vast Indo-Gangetic Plains (IGP) south of the Himalaya are subject to dense fog every year during winter months (December–January), severely disrupting rail, air and public transport of millions of people living in northern India, Pakistan, Nepal and Bangladesh. Air pollution combined with high moisture availability in the shallow boundary layer, are important factors affecting the persistence and widespread nature of fog over the IGP. Despite the environmental significance and impacts on the public at-large, an in depth understanding of the long-term spatial-temporal distribution of the south Asian fog, is presently not available in the literature. We utilize infrared remote sensing techniques to develop a high-resolution (≈1 km × 1 km) fog/low-stratus detection climatology over the past two decades (2002−2020), using Aqua/MODIS satellite observations. A dynamic brightness temperature difference threshold (involving 3.96 μm and 11.03 μm bands) for nighttime fog/low-stratus detection is constructed based on systematic radiative transfer simulations involving cloud effective radius, cloud top height, liquid water path and satellite viewing geometry. Our satellite-based fog/low-stratus detection is consistent with theoretical simulations of fog characterization and is also found to be well-correlated with near-surface visibility observations of dense fog (r = 0.89, p-value << 0.01). We also provide satellite-derived nighttime estimates of fog/low-cloud effective radius that are comparable to the operational daytime MODIS cloud data product and limited in situ observations. In terms of fog/low-stratus frequency, the IGP is relatively uniformly covered by widespread fog/low-stratus occurrences with the largest frequency found in the low-lying Terai region, bordering India and Nepal, which is also consistently observed in our daytime fog/low-stratus detection results over the last two decades. Additionally, the interannual variations in fog/low-stratus occurrences track closely with that of relative humidity in the IGP, which is associated with shallow boundary layer conditions during winter-time favoring the formation and persistence of fog. Overall, these long-term satellite-derived results present new high-resolution data and insights into the dense and often intense winter fog occurrences which routinely engulf the entire stretch of the Indo-Gangetic Plains and cause significant degradation to ground visibility in one of the world's most densely populated regions. •Development of a high-resolution (1 km × 1 km) fog data record over south Asia.•Mapping and quantifying winter fog occurrences from 2002 to 2020 using MODIS data.•Both nighttime and daytime spatial-temporal distribution of fog cover is generated.•Satellite-derived fog detection results closely track ground-observed poor visibility.